2017
DOI: 10.1126/science.aan4526
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic colonization of oral bacteria in the intestine drives T H 1 cell induction and inflammation

Abstract: Intestinal colonization by bacteria of oral origin has been correlated with several negative health outcomes, including inflammatory bowel disease. However, a causal role of oral bacteria ectopically colonizing the intestine remains unclear. Using gnotobiotic techniques, we show that strains of Klebsiella spp. isolated from the salivary microbiota are strong inducers of T helper 1 (TH1) cells when they colonize in the gut. These Klebsiella strains are resistant to multiple antibiotics, tend to colonize when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
621
4
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 686 publications
(651 citation statements)
references
References 41 publications
23
621
4
3
Order By: Relevance
“…In addition, increased levels of bacteria originating from the oral cavity have been reported in the gut microbiota of patients with liver cirrhosis and colorectal cancer, which suggests the existence of an oral‐gut connection. Moreover, it is reported that colonization of oral bacteria in the intestine results in the inflammation by inducing Th1 cells . Thus, oral bacteria can reach the gut and have the potential to induce an immune response.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, increased levels of bacteria originating from the oral cavity have been reported in the gut microbiota of patients with liver cirrhosis and colorectal cancer, which suggests the existence of an oral‐gut connection. Moreover, it is reported that colonization of oral bacteria in the intestine results in the inflammation by inducing Th1 cells . Thus, oral bacteria can reach the gut and have the potential to induce an immune response.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that ectopic localization of human salivary microbiota can elicit severe gut inflammation in susceptible host animals (48). It is therefore possible that ectopic oral microbiota could also exert a proinflammatory role in the context of SIgAd.…”
Section: Of 15mentioning
confidence: 99%
“…Recently, many studies regarding the relationship between oral bacteria and systemic diseases have been published . Oral bacteria can reportedly cause aspiration pneumonia, endocarditis, and artificial joint replacement surgery infections .…”
Section: Introductionmentioning
confidence: 99%